IoT Based Automatic Student Attendance Monitoring System - Chandrappa, S; Dharmanna, L; Deekshith, K; Jagadeesha, S (International Journal of Computer Sciences and Engineering, 2025)
Today, students (class) attendance is become more important part for any organizations/institutions. Recording and monitoring of class attendance is an area of administration that requires significant amounts of time and effort in a school/university environment. To solve this problem we are using RFID technology. RFID technology is a powerful tool to manage student‘s attendance throughout the working school day and it will also enhance classroom security. RFID is a technology that allows for a tag affixed on identity card of student to communicate wirelessly with a reader. Reader will read the tag number and send to raspberry pi. Program running in raspberry pi will mark the corresponding student to present. At the end, SMS notification is send to all students’ parents those who are absent.